2016
DOI: 10.3109/09638237.2016.1167858
|View full text |Cite
|
Sign up to set email alerts
|

“Very much evolving”: a qualitative study of the views of psychiatrists about peer support workers

Abstract: This study provides insights into how PSWs are perceived by psychiatrists. While broadly positive attitudes exist, the research highlights certain challenges, particularly role ambiguity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 19 publications
4
48
0
2
Order By: Relevance
“…19 Recovery-focused models are traditionally thought to contrast with diagnosis, but many clinicians who value diagnoses are supportive of recovery approaches. 28 Our model could inform the diagnostic process to be conducted in a way that is concordant with recovery principles. It particularly supports collaboration, person-centred care, and service user agency and empowerment, reflecting recommendations about service user participation.…”
Section: Discussionmentioning
confidence: 89%
“…19 Recovery-focused models are traditionally thought to contrast with diagnosis, but many clinicians who value diagnoses are supportive of recovery approaches. 28 Our model could inform the diagnostic process to be conducted in a way that is concordant with recovery principles. It particularly supports collaboration, person-centred care, and service user agency and empowerment, reflecting recommendations about service user participation.…”
Section: Discussionmentioning
confidence: 89%
“…Peer support may not become properly embedded in routine clinical practice if stakeholders are unwilling to integrate it into existing practice or unable to make sense of the information required to operationalise it effectively [20]. Yet, there remain concerns about the organisation and implementation of peer support, with some professionals describing peer support colleagues as increasing workload [21,22]. A non-systematic review of the barriers to PSW implementation identified a range of challenges, including cultural impediments, poor organisational arrangements, and inadequate overarching mental health policies [23].…”
Section: Introductionmentioning
confidence: 99%
“…A key part of recovery care-oriented approaches is an emphasis on the importance of consumer participation in shared decision-making (Simmons et al 2017). Peer support has been referred to as a wellness model in which individuals with shared experiences support others in recovery (Collins et al 2016;Gillard & Holley 2014) to reduce mental health stigma (Vayshenker et al 2016) and promote increased social inclusion (Lucksted et al 2009). This has been attributed to two essential features: '(i) people who share similar experiences can also share a common understanding of these experiences and can thereby be very helpful to each other and (ii) this sense of mutual understanding may be especially valued when it takes place within a broader context and history of feeling misunderstood' (Stratford et al 2017, p. 1).…”
Section: Introductionmentioning
confidence: 99%